Análisis financiero a la comercializadora Dicavi Cía. Ltda. “Camovi”, de la ciudad de Loja, período 2021-2022. - Valdez Herrera., Paula Adriana (2024)
The document for Curricular Integration called “Financial analysis of the commercialization company Dicavi Cía. Ltda. ‘Camovi’ in the city of Loja, period 2021-2022”, was developed with the objective of knowing the financial health through its economic-financial structure by applying the vertical and horizontal analysis and financial indicators, measuring the level of liquidity, solvency, management and profitability. The methodology was used through a mixed approach of exploratory-descriptive type with a correlational design, using the scientific method which gave a collection of theoretical content for the application of the Curricular Integration Document; the analytical method facilitated the examination and interpretation of each one of the accounts from the Financial Statements; techniques such as observation, interview and bibliographic review were applied; and, to perform the results, mathematics science and Excel program were used. The fulfillment of the objectives was carried out through the application of vertical and horizontal analysis, determining that in the financial structure for the period 2021-2022 the Current Assets subgroup is the most representative with an increase of $403,827.48 due to credit sales. The Current Liabilities subgroup shows a greater incidence due to the large amount of debt, it increased by $476,746.21 and the Net Equity decreased by $22,141.40 due to the reduction in accumulated profits. Within the economic structure there was an increase from one year to the next one of an amount in the Incomings of $ 1,304,664.76, the Costs of $ 1,289,641.60 and the Expenses of $ 77,775.52. When the financial indicators were established, it was determined that the company has moderate liquidity; it faces difficulties in terms of solvency; its management efficiency stands out in the inventory control and management of receivable accounts and portfolio; it obtained profitability in both years, but in the last period it registers a lower level. The financial report is concluded with the preparation of the financial report, which reflects valuable information on the analysis carried out, serving as a guide in the decision making process by the shareholders and being positive for the future of the trading company.